Transforming Diabetes Care: The Role of Artificial Intelligence in Diabetes Mellitus Management - Kajol; Abhijeet Singh Rana; Aditi Kaushik; Nikhil Sharma (International Journal of Progressive Research in Science and Engineering, 2024)
Diabetes is a chronic and complex metabolic disease that poses a significant health problem worldwide. Recent advances in artificial intelligence (AI) promise to improve the management and treatment of diabetes. This article explores various aspects of the role of intelligence in improving diabetes care, including predictive analytics, personalized care planning, and ongoing care. AI-powered tools can now analyse large amounts of patient data to predict the onset of diabetes, optimize insulin use, and provide instant advice from wearable devices. In addition, machine learning algorithms increase the accuracy of blood sugar monitoring and make it easier to detect problems early. Despite this progress, there are problems such as data privacy, integration with existing health systems, and ensuring equality. This article discusses the current state of AI applications in diabetes care, reviews research literature demonstrating its effectiveness, and offers recommendations that predict and potentially influence adoption. Finally, the integration of artificial intelligence into diabetes management promises to improve patient outcomes and reduce the burden of this disease.